Campanha De Vacinação Contra A Covid-19: Uma Análise Semiolinguística Dos Discursos Veiculados Pelo Ministério Da Saúde (PERcursos Linguísticos, 2022)
This paper aims to analyze the vaccination campaigns released, in video, bythe Ministry of Health on its YouTube channel. Thus, we aim to observe how the speechesbroadcast in the videos were constructed when trying to convince people to get vaccinated.For this, we made a corpus clipping, choosing 3 videos that represent the initial phase of thecampaign. Data analysis and discussions followed the assumptions of the analytical categoriesof Patrick Charadeau's Semiolinguistic Theory. We sought to identify the subjects involved inthe discourses, the elements of the communication contract and the discursive strategies thatwere used. The results of the analyses showed that in the videos there is a recurrence ofthemes related to work, the presence of a rural imaginary and the absence of scientificevidence related to the pandemic. Furthermore, in addition to encouraging the public to bevaccinated, the campaign served as a means of disseminating the actions of the Ministry ofHealth, also reinforcing guidelines on care with the pandemic. It is also worth noting that thespeeches in the videos are close to the ideals of the